Ecclesiological views of St. Hilarius of Arles in the context of the relationship between the Gallic churches and the Roman See in the mid-5th century - Georgy Zakharov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2024)
This article is devoted to the reconstruction of the ecclesiological views of St. Hilarius of Arles, who entered into a sharp conflict with the Roman Pope St. Leo the Great in the middle of the 5th century. Hilarius was the author of “The Life of St. Honoratus”, his relative, spiritual mentor and predecessor in the See of Arles. This text has a programmatic character. The hagiographer brings together the ascetic ideal and pastoral ministry, offering an ascetic-personalistic model of the local Church. The church community is constituted around the ascetic bishop and the circle of his disciples. Within the framework of this approach, the bishop’s connection with the local church tradition and the unanimous consent of the community to the election of a new bishop give way to the personal holiness of church leader, who pastorally reorganizes the community on new, ascetic foundations. Church succession is also interpreted rather as fidelity to the legacy of the holy bishop. This kind of model of the local Church did not fit into the ecclesiological conception defended by the Roman See, based on the idea of a consensus between the clergy and the people in the episcopal elections and historical episcopal succession in the local Church, as well as on the universal significance of the apostolic see, the actions of which are determined by the will of the Apostle Peter.